Desafios na introdução à geometria e às construções geométricas na educação básica - Freitas, Samuel Magalhães de (2021)
The objective of this work is to investigate the possibility of developing a methodological proposal to better involve students in studies and learning geometry, in order to awaken in the student motivation for investigative and deductive procedures. In this work we show, through constructions with ruler and compass, that it is possible to explore concepts, properties and improve the understanding of geometric concepts of students. As a theoretical framework for analysis, we take Van Hiele's theory as a basis and, for the methodological conduct of data collection and production, we are inspired by the principles of Didactic Engineering, described by Artigue. Thus, after preliminary studies of didactic texts and research work already carried out on the theme,we have elaborated a sequence of activities that involves the construction of parallel lines, perpendicular lines, bisectors and mediators with students from the 8th year of Elementary School. The application and analysis of the activities carried out with the students allowed us to observe that the students were involved in the proposed activities and expanded their knowledge about the geometric concepts treated, as well as the motivation to learn new concepts. In this work we seek to value both theoretical and practical aspects and we hope that it will serve as a basis for elementary school mathematics teachers, in their classroom practices when addressing Geometry content, since these resources are easily accessible and can instill curiosity of students regarding the use of these drawing instruments and the validity of geometric properties.